Compulsive technology use: Compulsive use of mobile applications. (October 2018) - Clements, Jeffrey A.; Boyle, Randall
Abstract: Information technology engages users beyond traditional organizational contexts. Technology has become more interconnected and personalized. As individuals are increasingly exposed to the types of triggers that prompt automatic technology engagement. Technology use has moved beyond the bounds of intentionality. This leads to the development of technology-use behaviors that may become automatic or difficult to control. Individuals can begin to develop spontaneous-use behaviors and feel compelled to interact with the systems they use. This study explores this phenomenon in the context of mobile applications, and conceptualizes this new type of system interaction as compulsive technology use. A theoretical framework of automatic behaviors is used to identify key technological mechanisms of behavioral initiation and psychological mechanisms of behavioral persistence, which contribute to compulsive technology use. The roles of technology habit and perception of sunk costs in the development of compulsive technology use are addressed. Characteristics and features of technology that influence compulsive technology use are identified. Highlights: Technology habit contributes to compulsive technology use. Technology complexity reduces technology habit. Technology cuing triggers contribute to technology habit.